AN OVERVIEW OF ANALYTICAL INSTRUMENT QUALIFICATION WITH REFERENCE OF PHARMACEUTICAL INDUSTRY - Kapoor, Devesh; Vyas, Ruchi B.; Dadrwal, Diwaker (Journal of Drug Delivery and Therapeutics, 2018)
In the most general sense, validation refers to a process that consists of at least four distinct components or steps: software, instruments, methods or procedures, and system suitability The system, the software, and the method must all be validated, and system suitability is used to keep the process in check. But while the overall process is called validation, some of the steps also are referred to by that same term, as well as other steps such as qualification and verification. Analytical instruments are used for a specific analysis. So regular performance verifications are made to ensure that the instrument to be used is suitable for its intended application. All equipments used in the production of products shall be properly Validated and Calibrated to demonstrate that it is suitable for its intended purpose. The current equipment qualification programs and procedures used within the pharmaceutical industry are based on regulatory requirements, voluntary standards, vendor practices, and industry practices. The result is considerable variation in the way pharmaceutical companies approach the qualification of laboratory equipment and the way they interpret the often vague requirements. The process for instrument qualification follows the 4Qs model approach. It include design qualification (DQ), Installation qualification (IQ), Operational qualification (OQ), Performance qualification (PQ). The goal of any regulated laboratory is to provide reliable and valid data suitable for its intended purpose. Analysts use validated methods, system suitability tests, and in-process quality control checks to ensure that the data they acquire are reliable and that there are specific guidance and procedures available to ensure compliance. Keywords: Qualification, FDA, Instruments, Validation, Calibration, Documentation